2016
DOI: 10.1051/epjconf/201611402095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the heating surface enhancement on the heat transfer coefficient for a vertical minichannel

Abstract: Abstract. The aim of the paper is to estimate effect of the heating surface enhancement on FC-72 flow boiling heat transfer for a vertical minichannel 1.7 mm deep, 24 mm wide and 360 mm long. Two types of enhanced heating surfaces were used: one with minicavities distributed unevenly, and the other with capillary metal fibrous structure. It was to measure temperature field on the plain side of the heating surface by means of the infrared thermography and to observe the two-phase flow patterns on the enhanced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…15÷80 µm (with an average being 40÷65 µm); the density of the solder paste -2990 kg/m 3 , the thickness of the soldered layer -approx. 100 µm and the maximum height of the soldered layer -200 µm [27]. …”
Section: The Tested Porous Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…15÷80 µm (with an average being 40÷65 µm); the density of the solder paste -2990 kg/m 3 , the thickness of the soldered layer -approx. 100 µm and the maximum height of the soldered layer -200 µm [27]. …”
Section: The Tested Porous Surfacesmentioning
confidence: 99%
“…Finally, the formation of vapour bubbles can be responsible for the reduction in heat transfer efficiency [27]. In the case of the surface formed by iron powder soldering, thermal resistance additionally occurs at the contact zones between the substrate and solder and between the solder and Fe powder grains.…”
Section: E3s Web Of Conferencesmentioning
confidence: 99%
“…One of the methods of heat transfer enhancement involves heat transfer surface modification. The modification causes the increase of heat transfer coefficient values through increasing the number of active nucleation sites during flow boiling [1][2][3][4][5][6][7][8][9][10] or pool boiling [10][11][12]. Modified surfaces exhibit reduced surface superheating and improve heat dissipation by increasing the area of heat removal.…”
Section: Introductionmentioning
confidence: 99%
“…In their previous articles, the authors of this paper reported their findings concerning various enhanced heat transfer surfaces with the flow of various working fluids through rectangular heat exchangers with minichannels. The surfaces studied included laser-textured surfaces with regular recesses [2,7], vibration-assisted laser-textured surfaces [3,4,6], surfaces with irregular recesses obtained in the process of spark erosion [1,2,5,6,10,11], surface with capillary-fibrous structure [1] and powder surfaces produced by sintering or soldering [8,9]. Based on the research results for flow boiling in minichannels, this article discusses the enhanced surfaces used, along with their production methods and effects on heat transfer processes.…”
Section: Introductionmentioning
confidence: 99%